Многоканальные устройства цифровой обработки сигналов с ранжированной архитектурой - Baranov, P. E.; Sheik-Seikin, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The architecture synthesis method is proposed for multichannel digital signal’s processing units under an effect of the complex interference, functioning in conditions of limits of the probing signal total energy and time of the controlled space viewing. It is shown that devising architecture provides considerable (in several times) reducing equipment’s recourse of the designing units.